Efektivitas Kewenangan Administratif Balai Pelestarian Kebudayaan Wilayah VIII dalam Pengelolaan Situs Banten Girang - Mailucky Fadrian Safitri; Nurikah Nurikah; Ahmad Rayhan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the effectiveness of the Regional Cultural Preservation Office Region VIII in managing the Banten Girang Site as an effort to preserve cultural heritage within the framework of legal protection and administrative governance. This research applies an empirical juridical method with a qualitative descriptive approach through interviews, and document analysis. The findings indicate that the management of the Banten Girang Site has been implemented through preventive preservation measures, periodic technical assessments, supervision by site custodians, and limited public outreach activities. However, the implementation has not yet reached optimal effectiveness due to several constraints, including unclear administrative authority, limited budget support, inadequate infrastructure, and suboptimal inter-institutional coordination. The study further identifies that sustainable preservation requires legal certainty, institutional harmonization, stronger fiscal support, community participation, and revitalization of supporting facilities. The findings affirm that effective cultural heritage preservation depends on the integration of legal substance, institutional capacity, administrative consistency, and public awareness. Strengthening collaborative governance is therefore essential to ensure the long-term sustainability of the Banten Girang Site as a historical and educational asset.